Determinants of Muslim Customers’ Preferences towards Islamic Banks Products and Services - Rayna Kartika; Fidya Kasih Maulidya (Fakultas Ekonomi Universitas Andalas, 2021)
As Indonesia has the biggest Muslim population in the world, Islamic banks starts to bloom in Indonesia rapidly. This paper aims to investigate the determinants of Muslim people to be customers of Indonesian Islamic banks. The determinants which are empirically tested are product knowledge of Islamic bank, product information dissemination, the profit margin of Indonesia Islamic banks, and service quality provided by Indonesia Islamic banks towards the preferences of Muslim people to be customers of Islamic banks. This research uses quantitative design which there are 155 samples conducted in this research and analyzed using SPSS. The sampling technique is purposive sampling where there are some criteria required to obtain respondents. The findings show that product knowledge, product information dissemination, and profit margin affect the preferences of being Islamic banks’ customers while service quality does not affect the preferences of being Islamic banks customers.